2015
DOI: 10.14260/jemds/2015/1493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Retrograde Intrarenal Surgery (Rirs) and Percutaneous Nephrolithotomy (Pcnl) in the Treatment of Single Renal Stone 2 - 3cm

Abstract: CONTEXT: Open surgery has given way to endoscopic surgeries. PCNL makes its way puncturing renal parenchyma where there is an unknown factor of damaging a major blood vessel. This may be overcome by retrograde intrarenal surgeries (RIRS) but the instrument has to traverse a long way through natural orifice and lumen. Which is less harmful and more helpful. AIM: To compare results from RIRS and PCNL in treating renal calculi of 2 to 3cm. MATERIALS AND METHODS:Retrospective analysis of consecutive patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…The rate of the Hb drop after surgery was significant between the two groups (P value 0.0001). Other studies showed that the rate of the Hb drop is approximately around 1.2 gm, in our study the rate of the Hb drop was around 0.6 gm/dl in both group collectively but was relatively higher in miniPCNL group which is lower than other studies [ 5 , 17 , 18 ].…”
Section: Discussioncontrasting
confidence: 74%
“…The rate of the Hb drop after surgery was significant between the two groups (P value 0.0001). Other studies showed that the rate of the Hb drop is approximately around 1.2 gm, in our study the rate of the Hb drop was around 0.6 gm/dl in both group collectively but was relatively higher in miniPCNL group which is lower than other studies [ 5 , 17 , 18 ].…”
Section: Discussioncontrasting
confidence: 74%